(untitled) (International Journal of Engineering and Computer Science, 2015)
Control systems have received exceptional attention in the industrial sector as they manage and regulate various systems. This paper is focused on the development of an IVR system for three phase motor control. A new approach is proposed for designing the protection and control unit of the three phase motor using the IVR systems. The main objective is to control the motor from a remote place u sing the mobile DTMF tone and also to receive the motor status feedback through SMS. GSM is found to be the most convenient, cost efficient network to be used for the transmission of the feedback signals at the motor end along with the generation of control signal by mobile DTMF. This control signal and the feedback SMS is transmitted through the GSM modem. Thus, this paper serves as an introduction to a new control technique of a three phase motor which can be effectively used for industrial purposes along with providing an SMS based alert system.